2001
DOI: 10.1159/000048545
|View full text |Cite
|
Sign up to set email alerts
|

Variable Sensitivity of Lymphoblastoid Cells to Apoptosis Induced by <i>Viscum album</i> Qu FrF, a Therapeutic Preparation of Mistletoe Lectin

Abstract: Background:Viscum album (VA) Qu FrF preparation consists of an aqueous extract of Viscum album, the European mistletoe. It has cytotoxic and immunomodulatory properties that support its usefulness in cancer therapy. However, only little information is available on the interaction between mistletoe lectin (ML) and the humoral compartment of the immune system. Methods: Inhibition of proliferation of cells was performed by incorporation of 3H-thymidine, and cell viability was assessed by the uptake of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…An in vitro study has suggested no risk of safety expected from the exposition of cancer cells to chemotherapeutic drugs and Viscum album extract simultaneously [ 19 ]. Dr. Kaveri’s group at Paris, France, has studied various cellular and molecular approaches to define mechanistic basis for the therapeutic benefit of Viscum album preparations, and they revealed that these preparations exert anti-tumor activities, which involve cytotoxicity, inhibition of angiogenesis associated with induction of apoptosis of endothelial cells, anti-inflammatory effect by inhibiting cytokine-induced PGE 2 secretion via selective inhibition of Cyclo-oxygenase-2 and other immunomodulatory mechanisms [ 20 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study has suggested no risk of safety expected from the exposition of cancer cells to chemotherapeutic drugs and Viscum album extract simultaneously [ 19 ]. Dr. Kaveri’s group at Paris, France, has studied various cellular and molecular approaches to define mechanistic basis for the therapeutic benefit of Viscum album preparations, and they revealed that these preparations exert anti-tumor activities, which involve cytotoxicity, inhibition of angiogenesis associated with induction of apoptosis of endothelial cells, anti-inflammatory effect by inhibiting cytokine-induced PGE 2 secretion via selective inhibition of Cyclo-oxygenase-2 and other immunomodulatory mechanisms [ 20 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to apoptosis thus becomes a hallmark of cancer (Evan et al, 2001). Plants are appreciated to be rich sources of unique compounds that can induce apoptosis in premalignant and malignant human cells by targeting various cellular components (Huyen et al, 2001). Significant anticancer activities have been identified from about 1000 plants and are yet to have their molecular mechanisms elucidated (Das et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis induction under VA action, as demonstrated in our study, may vary with the particular medicine preparation and cell type evaluated. [44][45][46] When the VA concentration was increased to 20 μL/mL, MSC viability decreased. The number of cells in initial apoptosis increased, causing cell death, which may be due to the release of cytochrome C to the cytosol, along with proteolytic activation of caspase-8, -9, -3 and -2, with a consequent reduction in the expression of anti-apoptotic molecules, as described in other studies.…”
Section: Discussionmentioning
confidence: 99%